2019
DOI: 10.7567/1347-4065/aafb51
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of electron beam evaporated a-Si films on textured glass substrates by flash lamp annealing

Abstract: We investigate the crystallization of amorphous silicon (a-Si) films, by flash lamp annealing (FLA), formed by electron beam (EB) evaporation on textured glass substrates. We confirmed that EB-evaporated a-Si films formed on textured glass can be crystallized by FLA. Optical reflectance on EB-evaporated a-Si can be reduced by using the textured glass, leading to a reduction in the fluence of a FL pulse required for the crystallization. The fluence of a FL pulse for the crystallization of EB-evaporated a-Si fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…27) In addition, due to the passivation effect of the SiN x film and the absence of the Cr adhesion layer, the thin-film poly-Si solar cells with higher conversion efficiency than those on Cr films will be obtained. 21) Figure 3 shows the surfaces of i-and n-poly-Si films on SiN x -coated textured glass after FLA at sub-pulse emission frequencies of 1, 2, 4, 6 and 10 kHz, respectively. All the samples have macroscopic stripe patterns and the width of the stripe changes with sub-pulse emission frequency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27) In addition, due to the passivation effect of the SiN x film and the absence of the Cr adhesion layer, the thin-film poly-Si solar cells with higher conversion efficiency than those on Cr films will be obtained. 21) Figure 3 shows the surfaces of i-and n-poly-Si films on SiN x -coated textured glass after FLA at sub-pulse emission frequencies of 1, 2, 4, 6 and 10 kHz, respectively. All the samples have macroscopic stripe patterns and the width of the stripe changes with sub-pulse emission frequency.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that EBevaporated a-Si films on glass substrates textured by RIE can be crystallized through EC. 21,22) Similar crystallization and anchor effect can also be seen when a Si nitride (SiN x ) film is inserted between a-Si and textured glass, which will act as a passivation and anti-reflection (AR) film for the back-contact cell. 22) In this study, we attempted to crystallize Cat-CVD a-Si:H films by FLA on SiN x -coated textured glass substrates.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Наиболее распространенным способом получения тонких пленок poly-Si на низкотемпературных подложках является кристаллизация пленок аморфного кремния (a-Si). Среди методов кристаллизации, которые используют прямое воздействие на исходную пленку кремния, можно выделить лазерный отжиг (laser annealing) [3], импульсный фотонный отжиг (flash lamp annealing) [4], отжиг термоплазменной струей (thermal plasma jet) [5], электронно-пучковую кристаллизацию (electron beam crystallization) [6,7].…”
unclassified